Genotoxicity of formaldehyde: molecular basis of DNA damage and mutation - Kawanishi, Masanobu; Matsuda, Tomonari; Yagi, Takashi (Frontiers in Environmental Science, 2014)
Formaldehyde is commonly used in the chemical industry and is present in the environment, such as vehicle emissions, some building materials, food and tobacco smoke. It also occurs as a natural product in most organisms, the sources of which include a number of metabolic processes. It causes various acute and chronic adverse effects in humans if they inhale its fumes. Among the chronic effects on human health, we summarize data on genotoxicity and carcinogenicity in this review, and we particularly focus on the molecular mechanisms involved in the formaldehyde mutagenesis. Formaldehyde mainly induces N-hydroxymethyl mono-adducts on guanine, adenine and cytosine, and N-methylene crosslinks between adjacent purines in DNA. These crosslinks are types of DNA damage potentially fatal for cell survival if they are not removed by the nucleotide excision repair pathway. In the previous studies, we showed evidence that formaldehyde causes intra-strand crosslinks between purines in DNA using a unique method (Matsuda et al. Nucleic Acids Res. 26, 1769-1774,1998). Using shuttle vector plasmids, we also showed that formaldehyde as well as acetaldehyde induces tandem base substitutions, mainly at 5’-GG and 5’-GA sequences, which would arise from the intra-strand crosslinks. These mutation features are different from those of other aldehydes such as crotonaldehyde, acrolein, glyoxal and methylglyoxal. These findings provide molecular clues to improve our understanding of the genotoxicity and carcinogenicity of formaldehyde.